Socio-Cultural Factors Affecting Livelihood of Staff Nurses in Lahore, Punjab Pakistan - Muhammad Nafees, Madiha Naz, Faiza Anjum, Muntazir Mehdi, Safder Abbas, Aamir Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The working women in under-developing nations face multiple issues due to their conservative socio-cultural setup. It not only affects the status of women but also hinders regional socio-economic development. Despite being significant contributors to healthcare, nurses are not treated well in society and also at their workplace. The maltreatment adversely affects their livelihood which ultimately affects the efficiency of healthcare. Objectives: Major objective of the study was to examine the socio-cultural factors affecting the livelihood of staff nurses, and to suggest suitable policy measures to address the issue. Material and methods: Using a qualitative research approach, this study was conducted in Lahore, the capital of Punjab province, Pakistan. Through multistage sampling, one hundred and fifty staff nurses were conveniently interviewed for data collection using a well structure Interview Schedule. The data collection tool was designed according to the Sustainable Livelihood Framework of DFID. The data were analyzed using descriptive statistics, and multivariate linear regression analysis using Statistical Package for Social Sciences (SPSS) version 21. Results: The irritating behavior of the patients, coworkers, and relatives, inability to attend social gatherings and harassment were negatively associated with the livelihood of the respondents. Conclusion: The socio-cultural factors had a negative impact on the livelihood of staff nurses. There is a dire need to make policies to change the attitude of the people towards this profession.